Pengaruh Model Pembelajaran Kooperatif Tipe Snowball Throwing Terhadap Hasil Belajar IPA di Sekolah Dasar - Widiyono Aan; Nihlatun Nakiyah; Khoirul Amri (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2023)
This research has a background in the science learning process which is still passive from interactions between students in discussions. The learning process is still teacher-centered which causes student learning outcomes to be less than optimal. The purpose of this study was to determine the learning outcomes of fifth grade students in science subjects in applying the snowball throwing model at SD Al Islam Pengkol Jepara. This type of research is quantitative research. The sample of this research is 25 class students. The data collection technique was carried out by giving questions in the form of a pretest and posttest. Meanwhile, the data analysis technique used prerequisite test and hypothesis test (t test). The results of this study note that the pretest value before applying the Snowball throwing model obtained an average of 64.2 and an average posttest value of 77.4. This is evidenced by the results of the analysis of hypothesis testing obtained a significant value (2-tailed) of 0.000 and an α value of 0.05, which means a significance value <0.05 or 0.000 <0.05. It can be concluded that there is an influence of the application of the snowball throwing cooperative model on science learning outcomes in class V SD Al Islam Pengkol Jepara.